Social and functional capacity of schizophrenia patients: A cross-sectional study. (June 2014) - Mohr, Pavel; Rodriguez, Mabel; Bravermanová, Anna; Melicher, Tomáš; Čeplová, Zuzana; Čermák, Jan; Pečeňák, Ján
Background: The chronic course of schizophrenia typically results in severe social, vocational and functional impairment, interferes with patients' autonomy, reduces quality of life and increases disability. Aims: The aim of our study was: (1) to assess social and functional impairment in schizophrenia outpatients from the Czech Republic and Slovakia; and (2) to examine a relationship between functioning and antipsychotic treatment and demographic variables. Methods: Schizophrenia outpatients in a stable phase of illness, treated with current antipsychotic medication for a minimum of one month, were enrolled for the study. Demographic and medication data were recorded. The Personal and Social Performance (PSP), Subjective Well-Being under Neuroleptics (SWN) and Clinical Global Impressions (CGI) scales were administered. Results: The total number of study subjects was 926. Most PSP values were within the interval of moderate impairment. Functional performance correlated positively with subjective satisfaction with medication and negatively with symptom severity. Higher education predicted better functioning on PSP. The best performance was associated with a stable relationship and a useful work role. Patients who showed the best level of functioning were more likely to be treated with antipsychotic monotherapy. No difference among drugs in monotherapy was found in subjective satisfaction. Conclusions: The PSP values of stable schizophrenia outpatients indicated a moderate degree of impairment. Improvement of functional capacity remains one of the unmet needs of schizophrenia patients.